The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s10140-002-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Massive pulmonary embolism: a comparison of radiological and clinical characteristics and outcomes

Abstract: Patients with MPE usually present with dyspnea and hypoxemia, and most survive without thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The size and amount of a pulmonary artery thrombus is not an independent predictor of mortality in PE patients. [17][18][19] However, Matej 20) reported that the morphology of an immobile central pulmonary thromboemboli in a massive PE is an independent predictor of short term mortality. Although the thrombus burden is not associated with the clinical severity of PE, patients with collapsed massive PE appear to have extensive pulmonary artery thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The size and amount of a pulmonary artery thrombus is not an independent predictor of mortality in PE patients. [17][18][19] However, Matej 20) reported that the morphology of an immobile central pulmonary thromboemboli in a massive PE is an independent predictor of short term mortality. Although the thrombus burden is not associated with the clinical severity of PE, patients with collapsed massive PE appear to have extensive pulmonary artery thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only 2 of the evaluated dogs were hypercapnic, indicating that alveolar hypoventilation was not a common problem. In studies [23][24][25] of pulmonary thromboembolism in dogs and humans, high Pao 2 -Pao 2 was more common than was hypoxemia, suggesting that calculation of this variable results in improved detection of abnormalities in gas exchange. Calculation of the Pao 2 -Pao 2 is also useful because it can be used to follow response to treatment, although this was not performed in the study of this report.…”
Section: Discussionmentioning
confidence: 99%